An evaluation of sustainability and societal impact of high-power laser and fusion technologies: a case for a new European research infrastructure. (21st September 2021) - Atzeni, S.; Batani, D.; Danson, C. N.; Gizzi, L. A.; Perlado, M.; Tatarakis, M.; Tikhonchuk, V.; Volpe, L.
Abstract: Fusion energy research is delivering impressive new results emerging from different infrastructures and industrial devices evolving rapidly from ideas to proof-of-principle demonstration and aiming at the conceptual design of reactors for the production of electricity. A major milestone has recently been announced in laser fusion by the Lawrence Livermore National Laboratory and is giving new thrust to laser-fusion energy research worldwide. Here we discuss how these circumstances strongly suggest the need for a European intermediate-energy facility dedicated to the physics and technology of laser-fusion ignition, the physics of fusion materials and advanced technologies for high-repetition-rate, high-average-power broadband lasers. We believe that the participation of the broader scientific community and the increased engagement of industry, in partnership with research and academic institutions, make most timely the construction of this infrastructure of extreme scientific attractiveness.